The survival of hotels during the COVID-19 pandemic: a critical case study in Vietnam - Hoang, Thinh Gia (Serv Bus, 2021)
The remedies used for the COVID-19 pandemic such as travel restrictions and quarantine have created severe difficulties for the hotel industry. However, there is also a scarcity of effective response strategies for the tourism and hospitality industry. This paper introduces a responding strategy developed by a case hotel in Vietnam to help survive this troubled period. Marketing’s service-dominant logic and Bourdieu’s theoretical framework of habitus, capitals, and field are used to facilitate the analysis of findings. Our empirical analysis further highlights the development of the paid quarantine service in a case hotel, which can help both hotels and authorities in Vietnam to respond effectively to the pandemic.